Efecto de borde (bosque tropical lluvioso-cacaotal) en los caracoles terrestres (Mollusca: Gastropoda) - Mijail Pérez, A (Universidad de Costa Rica, 1994)
The number of terrestrial gastropod species was assessed in a plistine tropical rain rorest and its border with an abandoned cacao plantation. Three species were found in the forest and nine in the border. The Czekanowski il1dex of similarity was low (IC = 36%) and the biogeographical index was slightly higher in the forest (lB= 2, bordee 1.6).